2008
DOI: 10.1111/j.1749-7345.2008.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graded Levels of Carbohydrate on Growth and Survival of Largemouth Bass, Micropterus salmoides

Abstract: Excessive carbohydrates (CHO) in diets for largemouth bass (LMB), Micropterus salmoides, are suspected of accumulating glycogen in hepatocytes, which may result in liver dysfunction. This study evaluated the effect of graded levels of dietary CHO on growth, survival, and liver histology of LMB. One hundred feed-trained advanced fingerling LMB (128.5 6 21.5 g) were stocked into each of nine 3400-L polyethylene tanks. Tanks were randomly assigned one of three experimental diets containing different CHO levels (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 31 publications
7
57
1
Order By: Relevance
“…Similar findings were obtained in top mouth culter (Erythroculter ilishaeformis Bleeker) (Liu et al, 2008) and European whitefish (Coregonus lavaretus) (Vielma et al, 2003). However, some other studies reported no significant differences in gilthead sea bream (Sparus aurata) (Enes et al, 2008), largemouth bass (Micropterus salmoides) (Amoah et al, 2008) and grass carp (Ctenopharyngodon idellus) (Gao et al, 2010).…”
Section: Resultssupporting
confidence: 63%
“…Similar findings were obtained in top mouth culter (Erythroculter ilishaeformis Bleeker) (Liu et al, 2008) and European whitefish (Coregonus lavaretus) (Vielma et al, 2003). However, some other studies reported no significant differences in gilthead sea bream (Sparus aurata) (Enes et al, 2008), largemouth bass (Micropterus salmoides) (Amoah et al, 2008) and grass carp (Ctenopharyngodon idellus) (Gao et al, 2010).…”
Section: Resultssupporting
confidence: 63%
“…; Amoah et al. ), which we inferred may reduce the survival of fish subjected to the stress of capture and handling by anglers. Administering a high‐protein, low‐carbohydrate diet (i.e., live forage) has been suggested to relieve pale liver syndrome (Goodwin et al.…”
Section: Methodsmentioning
confidence: 68%
“…In diets FM‐24 and FM‐8, fish meal was replaced by varying levels of poultry by‐product meal, soybean meal, and blood meal (which was maintained ≤ 7% of total formulation in all experimental diets to maintain palatability). The three experimental diets were formulated to contain ≤ 20% carbohydrates to prevent liver vacuolization (Amoah et al 2008). The reduced carbohydrate levels of the experimental diets produced “slow sinking” pellets.…”
Section: Methodsmentioning
confidence: 99%